An introduction to design patterns in C++ with Qt 4 - Ezust, Alan (Bruce Perens' Open Source series., 2006)
Learn C++, Patterns, and Qt 4 Cross-Platform Development Master C++ and design patterns together, using the world's leading open source framework for cross-platform development: Qt 4. An Introduction to Design Patterns in C++ with Qt 4 is a complete tutorial and reference that assumes no previous knowledge of C, C++, objects, or patterns. You'll walk through every core concept, one step at a time, learning through an extensive collection of Qt 4.1-tested examples and exercises. By the time you're done, you'll be creating multithreaded GUI applications that access databases and manipulate XML files--applications that run on platforms including Windows, Linux, Unix, and Mac OS X. Best of all, you'll be writing code that's efficient, reusable, and elegant. Learn objects fast: classes, inheritance, polymorphism, and more Master powerful design patterns Discover efficient high-level programming techniques using libraries, generics, and containers Build graphical applications using Qt widgets, models, and views Learn advanced techniques ranging from multithreading to reflective programming Use Qt's built-in classes for accessing MySQL data Includes a complete C++ language reference.